2018 52nd Asilomar Conference on Signals, Systems, and Computers 2018
DOI: 10.1109/acssc.2018.8645281
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint Channel Charting for Wireless Networks

Abstract: Multipoint channel charting is a machine learning framework in which multiple massive MIMO (mMIMO) basestations (BSs) collaboratively learn a multi-cell radio map that characterizes the network environment and the users' spatial distribution pattern. The method utilizes large amounts of highdimensional channel state information (CSI) that is passively collected from spatiotemporal samples by the multiple distributed BSs. At each BS, a high-resolution multi-path channel parameter estimation algorithm extracts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 10 publications
0
54
0
Order By: Relevance
“…Channel charting (CC), as proposed in [16], is unsupervised and uses dimensionality reduction to perform relative positioning solely from CSI measurements, without the need of ground-truth position information. Recent extensions of CC include multi-point CC [24] for systems with simultaneous connectivity to multiple BSs and semisupervised CC with autoencoders [22], which enables the inclusion of partially-annotated datasets. The Siamese network proposed in this paper unifies supervised CSI-based neural-networkbased positioning with unsupervised CC in a single network architecture.…”
Section: Relevant Prior Artmentioning
confidence: 99%
“…Channel charting (CC), as proposed in [16], is unsupervised and uses dimensionality reduction to perform relative positioning solely from CSI measurements, without the need of ground-truth position information. Recent extensions of CC include multi-point CC [24] for systems with simultaneous connectivity to multiple BSs and semisupervised CC with autoencoders [22], which enables the inclusion of partially-annotated datasets. The Siamese network proposed in this paper unifies supervised CSI-based neural-networkbased positioning with unsupervised CC in a single network architecture.…”
Section: Relevant Prior Artmentioning
confidence: 99%
“…To handle this issue, multiple antennas are used at both the Tx and Rx terminals [3]. Note that UEs of type V2I can have more than one antenna; however, it is shown that one element at the UE can be used to construct an accurate MPCC [21].…”
Section: System Modelmentioning
confidence: 99%
“…CC is based on the assumption that statistical properties of MIMO channel vary relatively slowly across space, on a length-scale related to the macroscopic distances between scatterers in the channel, not on the small fading length-scale of wavelengths. In this regard, the CSI covariance matrix can be used to capture large-scale effects of the wireless channel based on the assumption that there is a continuous mapping from the spatial location p k of UE k to the covariance CSI R b,k [20,21]:…”
Section: Feature Extraction and Dissimilarity Matrixmentioning
confidence: 99%
See 2 more Smart Citations